Plant Growth Regulators - Frederick M. Fishel (EDIS)
This document discusses the meaning of the term “plant growth regulator,” patterns of use and provides a listing of plant growth regulators registered for use in Florida. This document is PI-102, one of a series of the Pesticide Information Office, UF/IFAS Extension. Original publication date February 2006.